Design of Highly Selective Platinum Nanoparticle Catalysts for the Aerobic Oxidation of KA‐Oil using Continuous‐Flow Chemistry. Issue 5 (2nd March 2016) - Gill, Arran M.; Hinde, Christopher S.; Leary, Rowan K.; Potter, Matthew E.; Jouve, Andrea; Wells, Peter P.; Midgley, Paul A.; Thomas, John M.; Raja, Robert
Abstract: Invited for this month′s cover is the group of Dr. Robert Raja at the University of Southampton, UK. The image shows the origin of spatially isolated and well‐defined platinum nanoparticles, within a microporous framework architecture, for the selective aerobic oxidation of KA‐oil to cyclohexanone, which is an important precursor in the manufacture of nylon‐6. The Communication itself is available at10.1002/cssc.201501264 . Abstract : "As with most important discoveries, this one originated at the Royal Oak…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201501264 . View the Front Cover here:10.1002/cssc.201600245 .